2019
DOI: 10.4314/bajopas.v11i2.23
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of heavy metals by leafy vegetables grown with industrial effluents: A review

Abstract: Vegetables are capable of taking up and accumulating heavy metals in their body. The concentrations of the metals increase as the soil available/background concentration increases as a result of human activities including discharge and dumping of industrial waste and effluents into environment. The aim of this review is to highlight the capability of the vegetables to take up and accumulate toxic heavy metals into their body as a result of industrial contami the water used for irrigation purpose and the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…These vegetables tend to absorb and accumulate higher concentrations of heavy metals when cultivated in metalcontaminated soil compared to uncontaminated soil, primarily through their root systems. Specifically, certain Brassica species, such as cabbage, are known to hyper-accumulate heavy metals in their edible tissues [42].…”
Section: Baf Values Of Cabbage Var Tiaramentioning
confidence: 99%
“…These vegetables tend to absorb and accumulate higher concentrations of heavy metals when cultivated in metalcontaminated soil compared to uncontaminated soil, primarily through their root systems. Specifically, certain Brassica species, such as cabbage, are known to hyper-accumulate heavy metals in their edible tissues [42].…”
Section: Baf Values Of Cabbage Var Tiaramentioning
confidence: 99%
“…9 A number of studies have demonstrated that polluted environments with heavy metals may cause certain vegetables, including cabbage and lettuce, to accumulate high concentrations of these metals. [10][11][12][13] Given the potential toxicity, recalcitrant nature, and cumulative behaviour of heavy metals; the frequency of vegetable consumption; and safety and health concerns, such research is essential. Primary objectives of this study were to:…”
Section: Introductionmentioning
confidence: 99%